Exporting in West Africa : a practical guide - Isemede, John. (Lagos : Malthouse Press, 2003)
The book is a guide to the export and import business in Nigeria between 1993 and 2003.
Includes bibliographical references and index.
oif 16/05/14, opc 30/08/16
Loan
Keywords: Export marketing; Exports; Africa, West